Exploring the Impact of River Pollution on Environmental Health in Central Java - Indonesia: A Narrative Literature Review and Sustainable Management Strategies - Sugiharto, Septiono Bangun; Ali, Khaidar; Rizaldi, Muhammad Addin (Universitas Ibn Khaldun Bogor, 2025)
The pollution of rivers in Central Java - Indonesia has become an urgent environmental issue, posing high risks to public health and ecosystems. This literature review study aims to evaluate the impact of river pollution on water quality and environmental health, as well as to identify effective sustainable management approaches. The study found that river pollution in Central Java is primarily caused by industrial waste, domestic waste, and agricultural activities. Industrial waste contains hazardous heavy metals, while domestic and agricultural waste leads to eutrophication, damaging aquatic ecosystems and reducing water quality. This decline in water quality directly impacts human health, increasing the incidence of waterborne diseases such as diarrhea and cholera. The sustainable management approaches implemented include strict regulation and law enforcement, community education programs, and the application of wastewater treatment technologies. Studies from the Netherlands demonstrate that an integrated approach to water management can significantly reduce pollution, while community-based waste management practices in the Philippines also offer relevant solutions. To enhance sustainable management in Central Java, recommendations include strengthening regulations, adopting environmentally friendly technologies, increasing domestic wastewater management capacity, engaging communities, and developing green infrastructure. By implementing these strategies, it is expected that the river water quality in Central Java can be improved, supporting environmental health efforts and community well-being.